Groundwater Quality Assessment in the Middle-Upper Pleistocene Aquifer - Le Diem Kieu; Pham Quoc Nguyen (Salehan Institute of Higher Education, 2024)
The study was conducted to assess groundwater quality and identify the main pollution sources of groundwater in Hau Giang province, Vietnam. Groundwater samples were collected at five locations (GW1-GW5) at qp2-3 aquifer in May and October 2022. Principal component analysis (PCA), cluster analysis (CA), water pollution index (WPI), and groundwater quality index (GWQI) were applied in the study. The results revealed that the groundwater quality was influenced by TDS, NH4+-N, permanganate index, and Fe. On the basis of WPI, GW2 and GW3 had the lowest water quality, exceeding a value of 1. The results of GWQI showed that groundwater quality was divided into three categories (excellent, poor, and unsuitable for drinking) in May and four categories (good, poor, very poor, and unsuitable for drinking) in October. The study also revealed seasonal variations in groundwater quality, particularly in GW5 (Vi Thuy district, Hau Giang, Vietnam). The CA results formed four water quality groups in both periods based on the similarity of groundwater parameters. PCA results presented that the three PCs explained 79.55% of the variation in groundwater quality. Three potential sources of pollution are derived from the discharge of wastewater (domestic, industrial, and agricultural), landfilling, and seawater intrusion. Doi: 10.28991/CEJ-2024-010-07-018 Full Text: PDF